How Stress Influences the Dynamic Plasticity of the Brain’s Extracellular Matrix - Laham, Blake J.; Gould, Elizabeth (Frontiers in Cellular Neuroscience, 2022)
Diffuse and structured extracellular matrix (ECM) comprise ~20% of the brain’s volume and play important roles in development and adult plasticity. Perineuronal nets (PNNs), specialized ECM structures that surround certain types of neurons in the brain, emerge during the postnatal period, making their development and maintenance potentially sensitive to experience. Recent studies have shown that stress affects diffuse ECM as well as PNNs, and that such effects are dependent on life stage and brain region. Given that the ECM participates in synaptic plasticity, the generation of neuronal oscillations, and synchronous firing across brain regions, all of which have been linked to cognition and emotional regulation, ECM components may be candidate therapeutic targets for stress-induced neuropsychiatric disease. This review considers the influence of stress over diffuse and structured ECM during postnatal life with a focus on functional outcomes and the potential for translational relevance.